Peer Group: A New Approach of Nursing Intervention - Suyanto Suyanto; Moses Glorino Rumambo Pandin (Universitas Islam Sultan Agung, 2021)
The development of nursing, especially related to the nursing intervention approach, is running so fast. This can be seen from the use of peer group support in nursing interventions in individual humans. The purpose of this literature is to find the impact of implementing nursing interventions using a peer group support approach. This literature review method uses JBI and Prisma on 120 articles taken from journal databases, namely Scopus, PubMed and ScienceDirect. From the articles analyzed, it was found that the application of peer groups can improve individual abilities both in psychological and behavioral aspects. The application of the peer group approach is able to be one of the approaches in the world of nursing in carrying out nursing actions today.